Образні засоби поезії Василя Голобородька - Тиха, Лариса; Tykha, Larysa (Східноєвропейський національний університет імені Лесі Українки, 2015)
У пропонованій статті проаналізовано різні типи метафоричних структур, що функціонують у поезії Василя Голобородька. В аналізованому матеріалі метафоричні образи достатньо динамічні завдяки частому вживанню дієслів. Значна частина дієслівних метафоричних структур – це персоніфікації. Окрім того, зауважено, що поширеним явищем індивідуального стилю В. Голобородька є іменникові сполуки метафоричного змісту, які, як доводить аналіз фактичного матеріалу, побудовані на зіставленні та порівнянні ознак і функцій об’єктів навколишньої дійсності, а також прикметникові сполуки з переносним значенням. he article about the analysis of different types of metaphor structures that are used in the poems of Vasyl Holoborodko. The combination of metaphors in author’s poems discover the anexpected connection of associations that are expressed by different parts of speech like nouns, verbs, adjectives. When analyzing the poems we could see that the metaphor features are quite dynamic because of using of verbs. The biggest part of the verb metaphor structures are the personifications. The most often thing in individual style of Vasyl Holoborodko is the noun combination of metaphor context. The most of genitive metaphors are based on comparing of things, features and functions of the objects that surround us. The adjectives as the metaphor epithets very often play key role in the general structure. In this case we are talking about the adjective metaphor that makes the poems more bright and expressive.
The Feature of Picturesque in Vasyl Holoborodko’s Poems.
Keywords: метафора; образні засоби; дієслівна метафора; генітивна метафора; метафоричний епітет; персоніфікація; the adjective metaphor; metaphor structures; the noun metaphor; the verb metaphor; individual style